Geographical, social and socio-economic assessment of the fishery industry in Vietnam (Fishery master plan project, sub-project II) : (Carl Bro Group, 1996)
The report provides a presentation of data collected, analyses performed, geographical, economic and social descriptions and findings as well as recommendations for consideration in further planning for development of the fiheries sector.